Microbial Pigments in the Food Industry—Challenges and the Way Forward - Sen, Tanuka; Barrow, Colin J.; Deshmukh, Sunil Kumar (Frontiers in Nutrition, 2019)
ABSTRACT- Developing new colours for the food industry is challenging as colourants need to be compatible with a foods flavour, safety, nutritional value and ultimately have minimal impact on the price of the product. In addition, a food colorant is preferably a natural rather than synthetic compound. Microorganisms already produce industrially useful natural colorants such as carotenoids and anthracyanines. Microbial food colourants can be produced at scale for relatively low costs. This review highlights the significance of colour in the food industry, why there is a need to shift to natural food colours compared to synthetic ones and how using microbial pigments as food colorants instead of colours from other natural sources is a preferable option. We also summarise currently used microbial derived food colorants and their classification based on their chemical structure. Finally, we discuss the challenges faced by the use and development of food grade microbial pigments and how to deal with these challenges, using advanced techniques including metabolic engineering and nanotechnology.